2009
DOI: 10.1128/mcb.00195-09
|View full text |Cite|
|
Sign up to set email alerts
|

MLL Associates with Telomeres and Regulates Telomeric Repeat-Containing RNA Transcription

Abstract: Mammalian telomeres consist of TTAGGG repeats organized in nucleosomes and associated with a sixprotein complex known as shelterin, which preserves telomere structure and protects chromosome ends from the cellular DNA damage response. Recent studies have found that telomeres are transcribed into telomeric UUAGGG repeat-containing RNA (TERRA) starting from subtelomeric regions. TERRA binding at telomeres appears to be involved in cis-based mechanisms of telomeric chromatin organization and maintenance. A number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
123
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 45 publications
5
123
1
1
Order By: Relevance
“…TERRA expression can be regulated by developmental and stress-related signals, including DNA damage and viral infection (7,(45)(46)(47). Telomere shortening may also increase TERRA expression (48), but it is not clear that senescent cells show a global increase in TERRA levels.…”
Section: Discussionmentioning
confidence: 99%
“…TERRA expression can be regulated by developmental and stress-related signals, including DNA damage and viral infection (7,(45)(46)(47). Telomere shortening may also increase TERRA expression (48), but it is not clear that senescent cells show a global increase in TERRA levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 TERRA induction can result from DNA damage, and a requirement for p53 (TP53) has been reported. 3 The p53 protein is a DNA-binding transcription factor with potent tumor suppressor properties. 5 In response to cell stress, p53 protein accumulates and binds to degenerate consensus sequences throughout the genome, activating the transcription of many target genes involved in DNA damage repair, apoptosis, and other cellular processes.…”
mentioning
confidence: 99%
“…[3][4][5] Recent studies have also found overall acetylation of H3 and H4 histone tails, H3K4 di-and trimethylation and H3K79 dimethylation at telomeres, which are permissive histone marks in defining transcribed chromatin regions and their promoter sequences, and in maintaining a transcriptionally active state. 6,7 The heterochromatic nature of telomeres, the low subtelomeric gene density, as well as the transcriptional silencing exerted Transcriptional regulation of telomeric non-coding RNA Implications on telomere biology, replicative senescence and cancer Corrado Caslini Departments of Pathology; University of Michigan Medical School; Ann Arbor, MI USA PoINt oF VIew di-and trimethylation. 7 Thus, it appears that the telomere length is dominant over telomere epigenetic state in modulating TERRA levels, suggesting a telomere length-dependent transcriptional regulation of TERRA.…”
mentioning
confidence: 99%
“…6,7 The heterochromatic nature of telomeres, the low subtelomeric gene density, as well as the transcriptional silencing exerted Transcriptional regulation of telomeric non-coding RNA Implications on telomere biology, replicative senescence and cancer Corrado Caslini Departments of Pathology; University of Michigan Medical School; Ann Arbor, MI USA PoINt oF VIew di-and trimethylation. 7 Thus, it appears that the telomere length is dominant over telomere epigenetic state in modulating TERRA levels, suggesting a telomere length-dependent transcriptional regulation of TERRA.…”
mentioning
confidence: 99%
See 1 more Smart Citation